Age-Specific Impact of Cribriform Pattern in Prostate Cancer Following Radical Prostatectomy - Ari S Hilibrand; Yetkin Tuac; Okan Argun; Christina M. Breneman; Michelle Oh; Shalini Moningi; Jonathan E Leeman; Mutlay Sayan (Clinical Medicine Insights: Oncology)
Background: Cribriform pattern 4 (CP4) is an aggressive variant in prostate cancer linked to worse clinical outcomes, including biochemical recurrence, metastases, and prostate cancer-specific mortality. However, its prognostic significance across age groups remains unclear. This study investigates whether the impact of CP4 on progression-free survival (PFS) differs by age in patients undergoing radical prostatectomy (RP). Methods: This retrospective analysis used patient data from the TCGA database, evaluating patients who underwent RP stratified by CP4 status. The primary outcome was PFS, defined as the time from RP to biochemical recurrence, radiographic progression, or death from any cause. Multivariable Fine-Gray competing risk regression analyses assessed the association between CP4 and PFS, adjusting for preoperative prostate-specific antigen (PSA), Gleason score, tumor stage, and surgical margin status. An interaction term between age (dichotomized at 60 years to facilitate clinical interpretation and applicability, approximating the cohort median age of 61 years [interquartile range = 56-66]) and CP4 status was included in the analysis. Results: Of 431 patients, CP4 was present in 134 (31%). In multivariable analysis, CP4 was associated with significantly worse PFS in patients older than 60 years (adjusted hazard ratio [AHR]: 1.99, 95% confidence interval [CI]: 1.01-3.92, P  < .001), but not in younger patients (⩽60 years; AHR: 1.00, 95% CI: 0.49-2.04, P  = .997). Adjusted 5-year PFS was significantly lower in older CP4-positive patients (50.8%, 95% CI: 33.0%-78.2%) compared with older CP4-negative patients (74.6%, 95% CI: 63.6%-87.6%; P  < .001). Conclusion: CP4 strongly predicts reduced PFS in patients above 60 years but not younger patients, suggesting that age may influence the clinical impact of CP4. These findings support age-specific risk stratification in CP4-positive prostate cancer. Prospective studies are needed to validate results and explore tailored treatment strategies based on age.